As atividades significativas e o cotidiano das pessoas em sofrimento psíquico pelo uso de álcool e outras drogas: perspectivas em Terapia Ocupacional - Carleto, Daniel Gustavo de Sousa (2025)
Drug use has been a part of humanity since ancient times, present in different cultures with different motivations. Harmful use can lead to fragility and the rupture of social bonds, isolation, and vulnerability in various aspects of people's lives. In this context, Occupational Therapy works to promote social reintegration and a meaningful daily life. Through activities that are meaningful to the individual, the aim is to rescue abandoned experiences and create possibilities, aiding in their recovery and social reintegration. This doctoral thesis aimed to understand the meaningful activities and daily lives of people suffering from psychological distress due to alcohol and other drug use from their own perspectives. The research, which used a qualitative approach, involved 10 people suffering from psychological distress due to alcohol and other drug use who attended a Psychosocial Care Center for Alcohol and Drugs in a municipality in the Triângulo Mineiro region. The theoretical framework used was the theory of everyday life proposed by Agnes Heller. Data were collected over a five-month period, specifically from February to July 2023, through a sociodemographic questionnaire and an adaptation of the Photovoice method. This consisted of asking participants to take photos of meaningful activities they perform, would like to perform, represent their daily lives, and would like to be part of their daily lives. The data collected through the sociodemographic questionnaire were analyzed descriptively. The data collected through the adapted Photovoice method and the interview guide were analyzed using thematic content analysis, from which three categories of analysis emerged: What is meaningful to do: human activities; A daily life of meaningful activities; Using drugs is a meaningful activity (yes)! The results showed that participants attributed different meanings to meaningful activities and daily life, including the use of psychoactive substances itself. Daily life was understood as a daily routine composed of various activities, in addition to care/assistance activities, interpersonal relationships, and work activities. The data revealed that drug use influences the performance of meaningful activities and the daily lives of participants, but that it can also be considered a meaningful activity in people's lives. The research findings demonstrated the relevance of the Alcohol and Drug Psychosocial Care Center and the development of feelings of belonging in the contexts in which people with psychological distress due to alcohol and other drug use live for the performance of meaningful activities and the redefinition of their daily lives. Based on the theoretical framework adopted, it was possible to analyze the influence of psychological distress and drug use on the daily lives of participants. The study demonstrates the importance of considering the perspectives of people with psychological distress due to alcohol and other drug use in valuing their meaningful activities and redefining their daily lives, enabling qualification for this area of Occupational Therapy.